Evaluasi Efektivitas Sistem Barcode Absensi Dalam Meningkatkan Kedisiplinan Siswa Mas Miftahussalam Medan - Yulitriani Yulitriani; Hadi Saputra Panggabean; Muhammad Yunan Harahap (Journal Of Dehasen Educational Review, 2026)
This study aims to evaluate the effectiveness of the barcode attendance system in improving student discipline at Mas Miftahussalam. This system is expected to improve discipline, punctuality, and regularity of student attendance in the madrasah environment. This study also identifies supporting and inhibiting factors in the implementation of the barcode attendance system in schools. The research method used is qualitative with data analysis techniques that include three stages: data reduction, data presentation, and conclusion drawing. The results show that the barcode attendance system is effective in improving student discipline, especially in the aspects of attendance and punctuality. This system is considered more practical and efficient than manual attendance and is equipped with automatic WhatsApp notifications to parents as a form of supervision. The main supporting factor is the active role of teachers on duty, while the inhibiting factor is the limited internet connection. Overall, the barcode system has been proven to be able to improve student discipline in madrasahs.